Takaful plan for E-Hailing: a comparison between the available private motor vehicle takaful plans in Malaysia - Asuhaimi, Fadhilah Abdullah; Khaliq, Ahmad; Mohd Sofian, Fatimah Noor Rashidah (Springer, Cham, 2023)
The era of digitalization and technology brings tremendous changes in most industries including e-hailing services. E-Hailing services receive a lot of attention as it helps people to commute from one place to another comfortably, with more flexibility, convenience, less cost and quicker compared to traditional public transport. E-Hailing offers public transportation services through an elec-tronic application. This medium allows e-hailing drivers to meet passengers and provide transportation services and also spend more time on the road. Eventually, e-hailing drives expose themselves to higher motor-related risks such as road accidents, attacks by robberies, threats or even hijacking. Hence, each e-hailing driver is urged to have an adequate takaful plan to be protected from any unfortunate events. Looking at the need to have a takaful plan for e-hailing service, this chapter aims to compare functional private motor vehicle takaful plans offered by existing takaful operators and suggests improvements on it. Comparative analysis was made to see any similarities and differences between the available private motor takaful in the market. The researcher believes this study enables e-hailing drivers to have wider options and sufficient coverage offered by takaful operators while driving and the results of the present research add value to the existing knowledge base